Knowledge, attitude and practice of dental students, interns and practitioners to the use of amalgam in a dental institution of Kathmandu, Nepal - Dixit, Punam Basnet; Dixit, Siddharth; Dahal, Sirjana; Poudel, Prakash; Ghimire, Siddharth; Koirala, Tribhuwan (Journal of Kathmandu Medical College, 2020)
Background: Dental practitioners of Nepal have been using amalgam for years for restoration, but the concern for mercury related health issues and inventions in metallurgy science have recently led to its decreased use. Objectives: To assess the knowledge, attitude and practice of students, interns and dentists to the use of dental amalgam in a dental institution of Kathmandu, Nepal. Methodology: A cross-sectional study was conducted in a dental institution of Kathmandu among 192 Dental students, interns, dental officers and dental specialists selected by census sampling method. Self-administered questionnaire consisting of 16 questions related to amalgam war, its use and safety was used. Data collected were analyzed using Statistical Package for Social Sciences version 20. Frequency and percentage were calculated for each response according to different professional levels. Results: Most of the respondents including all the dental officers did not use amalgam frequently for restoration (141, 73.44%). Mercury toxicity was their major concern that restricted amalgam use (60, 31.25%). Most of them, (135, 70.31%) agreed on stopping the use of amalgam. They were comfortable to use composite resin as an alternative to amalgam (185, 96.35%). Majority (123, 64.06%) considered amalgam to be an unsafe material and were bothered about the environmental issues of mercury in the dental office (152, 79.16%). Conclusion: This study concludes that amalgam was less frequently used for restoration due to the increasing concerns of mercury toxicity. Further studies on safety of other materials that can replace amalgam with long term follow up are necessary before they are considered as a definitive alternative for amalgam.